MicroRNAs regulate p21(Waf1/Cip1) protein expression and the DNA damage response in human embryonic stem cells - Dolezalova, Dasa; Mraz, Marek; Barta, Tomas; Plevova, Karla; Vinarsky, Vladimir; Holubcova, Zuzana; Jaros, Josef; Dvorak, Petr; Pospisilova, Sarka; Hampl, Ales (Stem cells (Dayton, Ohio), 2012)
Studies of human embryonic stem cells (hESCs) commonly describe the nonfunctional p53-p21 axis of the G1/S checkpoint pathway with subsequent relevance for cell cycle regulation and the DNA damage response (DDR). Importantly, p21 mRNA is clearly present and upregulated after the DDR in hESCs, but p21 protein is not detectable. In this article, we provide evidence that expression of p21 protein is directly regulated by the microRNA (miRNA) pathway under standard culture conditions and after DNA damage. The DDR in hESCs leads to upregulation of tens of miRNAs, including hESC-specific miRNAs such as those of the miR-302 family, miR-371-372 family, or C19MC miRNA cluster. Most importantly, we show that the hESC-enriched miRNA family miR-302 (miR-302a, miR-302b, miR-302c, and miR-302d) directly contributes to regulation of p21 expression in hESCs and, thus, demonstrate a novel function for miR-302s in hESCS. The described mechanism elucidates the role of miRNAs in regulation of important molecular pathway governing the G1/S transition checkpoint before as well as after DNA damage.
Keywords: inhibitor p21 cyklin-dependentní kinasy; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Blotting, Western; mikro RNA; buněčné linie; Humans; Cell Differentiation; Cell Line; koncové značení zlomů DNA in situ; Tumor Suppressor Protein p53; poškození DNA; DNA Damage; nádorový supresorový protein p53; embryonální kmenové buňky; In Situ Nick-End Labeling; MicroRNAs; western blotting; lidé; Cyclin-Dependent Kinase Inhibitor p21; buněčná diferenciace; Embryonic Stem Cells